Estação ferroviária Santa Clara - Saboia: redefinição do espaço arquitetónico - Barão, Gonçalo Jacinto (2020)
All the constructions in the railway industry attended to rules and standards previously established. Within all the railroad structures and infrastructures, the railway stations were a target of significant functional evolution, because of its direct relation with the population itself and the city. Model projects emerged determinating the base type of currently existing buildings. The absence of use by the population of this mean of transportation asserted the growth of the inactivity rate of railway stations and the consequent degradation of the infrastructure. Santa Clara-Sabóia Train Station, located in the County of Odemira, was a mark in the process of reactivation, in 2011, came to trigger the possibility to reactivate the engaging territory. It became intuitive of the necessity to analyze different typologies through the description of the railway complex and to define methods and actions that could allow the redefinition of the site by formal and functional rehabilitation of the present buildings; RESUMO: Na indústria ferroviária todas as construções obedeciam a regras, normas e tratados previamente estabelecidos. Entre todas as estruturas e infraestruturas, as estações ferroviárias foram alvo de uma maior evolução funcional pela sua direta relação com a população e com a cidade. Surgiram assim projetos-tipo que determinaram a base das edificações atualmente existentes. A falta de utilização da população deste meio de transporte afirmou o aumento da taxa de inatividade das estações e a consequente degradação da infraestrutura. A Estação Ferroviária de Santa Clara-Sabóia, localizada no Concelho de Odemira, alvo de um processo de reativação, em 2011, veio despoletar a possibilidade de reativação do território envolvente. Tornou-se evidente a necessidade de analisar as diferentes tipologias através da caracterização do conjunto ferroviário e definir métodos e ações que permitam a redefinição do lugar e a reabilitação formal e funcional dos edifícios em questão.